2018
DOI: 10.11152/mu-1565
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the common carotid artery wall stiffness by Shear Wave Elastography in Behcet’s disease

Abstract: Aim: To evaluate endothelial dysfunction and subclinical atherosclerosis in Behcet’s disease (BD) by measuring the common carotid artery (CCA) wall stiffness and carotid intima-media thickness (CIMT).Materials and methods: We prospectively evaluated CIMT and the CCA wall stiffness of 34 BD patients and 28 age/sex-matched controls. CIMT measurements were performed from the posterior wall of the carotid artery approximately 10 mm proximal to the initiation of the carotid bulb using B-mode ultrasound. The stiffne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 46 publications
0
15
0
3
Order By: Relevance
“…First, by the use of different US machines as acquisition and post-processing properties differ with the machine. Alis et al (2018) reported considerably lower stiffness values in the arterial wall than the other studies. They used a Toshiba Aplio 500 machine that does not have a specific carotid artery mode.…”
Section: Quantitative Stiffness Valuesmentioning
confidence: 52%
See 3 more Smart Citations
“…First, by the use of different US machines as acquisition and post-processing properties differ with the machine. Alis et al (2018) reported considerably lower stiffness values in the arterial wall than the other studies. They used a Toshiba Aplio 500 machine that does not have a specific carotid artery mode.…”
Section: Quantitative Stiffness Valuesmentioning
confidence: 52%
“…This difference disappeared when both groups were compared at similar blood pressures (Marais et al 2019). Behçet's disease (Alis et al 2018) was, independent of blood pressure, associated with a higher SWV compared with controls. In addition, stiffness values positively correlated with patient characteristics (i.e., age, systolic blood pressure and low-density lipoprotein) in patients with hypertension (Marais et al 2019) and ischemic stroke (Maksuti et al 2016).…”
Section: Feasibility and Valuementioning
confidence: 87%
See 2 more Smart Citations
“…When present, inflammation causes endothelial damage, thereby altering the vessel wall architecture, resulting in stiff vessels with a loss in vascular reactivity and as a consequence, impairment in cerebral auto-regulatory capacity. Elastography has the ability to measure such changes and has been used in inflammatory conditions such as Bechet's disease to demonstrate early subclinical vasculitis as suggested by greater vessel stiffness [59]. These early findings may serve to identify subclinical measures of pathologic inflammation sooner, thereby enhancing clinical detection and providing targets for earlier intervention, and prevention of secondary complications.…”
Section: Elastographymentioning
confidence: 99%